2015
DOI: 10.1016/j.jamda.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Oral Nutritional Supplementation Plus Physical Exercise Intervention on the Physical Function, Nutritional Status, and Quality of Life in Frail Institutionalized Older Adults: The ACTIVNES Study

Abstract: A 12-week intervention with oral nutritional supplementation plus physical exercise improves function, nutritional status, and quality of life in frail institutionalized older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 39 publications
4
91
0
20
Order By: Relevance
“…The way subjects are defined as malnourished or frail differs greatly among studies. Some studies use the phenotype model of frailty (Abizanda et al 2015;Tieland et al 2012), nutritional assessment or screening tools (Abizanda et al 2015;Kim et al 2013;Smoliner et al 2008;Stange et al 2013), or specific characteristics (e.g., BMI, reported weight loss) (Edington et al 2004;Neelemaat et al 2010;Payette et al 2002;Wouters-Wesseling et al 2003) for patient recruitment. Other studies simply report using frail populations without clearly defining the criteria for classification (Bonnefoy et al 2003;Gray-Donald et al 1995;Paw et al 2002;Payette et al 2002).…”
Section: Participants Included In Efficacy Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The way subjects are defined as malnourished or frail differs greatly among studies. Some studies use the phenotype model of frailty (Abizanda et al 2015;Tieland et al 2012), nutritional assessment or screening tools (Abizanda et al 2015;Kim et al 2013;Smoliner et al 2008;Stange et al 2013), or specific characteristics (e.g., BMI, reported weight loss) (Edington et al 2004;Neelemaat et al 2010;Payette et al 2002;Wouters-Wesseling et al 2003) for patient recruitment. Other studies simply report using frail populations without clearly defining the criteria for classification (Bonnefoy et al 2003;Gray-Donald et al 1995;Paw et al 2002;Payette et al 2002).…”
Section: Participants Included In Efficacy Studiesmentioning
confidence: 99%
“…Further, researchers rarely explicitly state malnutrition or frailty as an outcome, but rather use a combination of measures relating to both concepts (e.g., function, falls) without connecting them to the specific condition (Edington et al 2004;Neelemaat et al 2010). One exception was a study on ONS and physical exercise as the intervention (Abizanda et al 2015). Outcomes covered both malnutrition and frailty concepts with standardized diagnostic tools (e.g., Mini Nutritional AssessmentShort Form, Short Physical Performance Battery, Short-Form-Late-Life Function & Disability Instrument, and HGS).…”
Section: Choice Of Outcome Measuresmentioning
confidence: 99%
“…Studies have suggested that exercise and nutrition interventions can improve outcomes in frail older persons (72)(73)(74)(75). A rapid screen -the FRAIL -can be utilized both in hospitals (76,77) and in the outpatient setting (78)(79)(80)(81).…”
Section: Modern Geriatric Giantsmentioning
confidence: 99%
“…35 Cholecalciferol (vitamin D 3 ) should be administered at a dose of 800 IU/day or higher. [49][50][51][52][53] This is relatively inexpensive and achieves serum 25(OH) D concentrations >50 nmol/L in most subjects, so it can be implemented without baseline or follow-up measurement of serum 25(OH) D concentrations, which can be relatively expensive. Recent studies suggest that weekly doses of vitamin D may be more effective in correcting deficiency than small regular doses, have an effect on preventing both fractures and falls, and might achieve higher compliance, which is a major limitation of this therapy.…”
Section: Pharmacologicalmentioning
confidence: 99%